Study of Serum Insulin Level in Hypertensive Patients - Uddin, MN; Ali, MZ; Jahan, NWB; Rashid, MA; Sultan, MK; Hoque, MA; Rahman, MM (Cardiovascular Journal, 2012)
Background and aims: Hypertension is a frequent and almost ubiquitous health disorder, prevalent both in developed and developing countries. Hyperinsulinemia and insulin resistance have been suggested to be closely associated with the pathogenesis of essential hypertension. However there is considerable controversy in this regards. The present study was designed to explore the relationship between serum insulin and serum ionized calcium in non diabetic and diabetic hypertensive subjects. Subjects and Methods: A total of 57 hypertensive and diabetic hypertensive patients attending out patients department of the BIRDEM and NICVD were included in the study. Fasting serum glucose was measured by glucose oxidase method, lipid profile was measured by enzymatic method. Serum insulin was measured by Enzyme Linked Immunosorbent assay (ELISA) method and serum ionized calcium by the Ion Sensitive Electrode (ISE) technique. Results: Glucose-insulin ratios were calculated as the index for insulin. Serum insulin (pmol/ml), Mean ± SD, 147 ± 48 in DC and 170 ± 80 in DH groups vs 118 ± 21 in NC and 120 ± 41 in EH groups, p= 0.023 and p= 0.031 respectively. Although, from the serum insulin results, the diabetic groups seemed to have insulin resistance, the glucose-insulin ratios in the two groups were significantly lower compared to nondiabetic groups (Glucose-insulin ratio, mmol/pmol, 0.066 ± 0.025 in DC, 0.074 ± 0.025 in DH vs 0.044 ± 0.11 in NC, 0.043 ± 0.012 in EH, p= 0.005 - 0.0001). The serum ionized calcium in the healthy subject, first time reported in the country by an up to date method (1.17 ± 0.05 M ± SD), were within the range found in healthy subjects of the other populations. No significant difference in the serum Ca2+ could be found between any of the study groups. Also, serum Ca2+ did not correlate with blood pressure, glucose or insulin in any of the study groups or with all the patients as a whole. Serum total cholesterol, triglyceride, HDLc and LDLc levels in the DC, EH and DH group did not show any significant difference compared to NC group and among the groups. The lipid abnormality as reflected by the mean LDL-HDL cholesterol ratios was the highest in the DH group but the differences were not statistically significant compared to the NC, DC and EH group. Conclusions: The data suggest the following conclusions: a) Serum ionized calcium level in our population is similar to that reported for other population. b) Serum glucose and insulin by themselves do not have any direct influence on serum ionized calcium. c) Non obese diabetes mellitus subjects in our population do not show insulin resistance as the primary defect. Rather, there is significant decompensation of the insulin secretory capacity in the subjects. d) Insulin resistance should be measured directly in relation to blood pressure and Ca2+ in appropriate groups of subjects to explore the relationship between insulin resistance, hyperinsulinemia and serum ionized calcium. Keywords: Serum Insulin; Hypertension DOI: http://dx.doi.org/10.3329/cardio.v4i1.9384 Cardiovasc. J. 2011; 4(1): 13-16